2022
DOI: 10.1155/2022/2686992
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum Polysaccharide Regulates Macrophage Polarization and Improves LPS-Induced Acute Lung Injury through TLR4-MAPK/NF-κB Pathway

Abstract: Objective. To investigate the effects of polygonatum sibiricum polysaccharides (PSPs) on the polarization of macrophages to M1 and M2 phenotypes and their potential mechanism. Methods. PSPs samples were prepared through water extraction and alcohol precipitation assay. The properties of PSPs were identified and analyzed by high-performance liquid chromatography, FT-IR, and NMR assay. Then, the effects of PSPs on mouse macrophage RAW264.7 viability were measured by CCK-8 assay. The cells were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Multiple studies have indicated that TLR4 recognizes LPS and triggers the activation of the NF-κB signaling pathway, promoting macrophage polarization into the M1 phenotype [ [320] , [321] , [322] ]. The combination of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) and GEM is the primary treatment approach for patients with advanced pancreatic cancer [ 323 ].…”
Section: Modulation Of Tams By Nanomaterials For the Treatment Of Pan...mentioning
confidence: 99%
“…Multiple studies have indicated that TLR4 recognizes LPS and triggers the activation of the NF-κB signaling pathway, promoting macrophage polarization into the M1 phenotype [ [320] , [321] , [322] ]. The combination of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) and GEM is the primary treatment approach for patients with advanced pancreatic cancer [ 323 ].…”
Section: Modulation Of Tams By Nanomaterials For the Treatment Of Pan...mentioning
confidence: 99%
“…11 A previous study has documented that miR-9-5 p promotes M1 macrophage polarization and inhibits M2 macrophage polarization. 12 Nevertheless, the efficacy of miR-9-5 p in ALI remains to be elucidated. The study was designed to assess the efficiency of miR-9-5 p in ALI via the modulation of macrophage polarization, thus offering insightful therapeutic modalities for ALI treatment.…”
Section: Introductionmentioning
confidence: 99%